2017
DOI: 10.1016/j.ejcb.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The two Dictyostelium discoideum autophagy 8 proteins have distinct autophagic functions

Abstract: Autophagy is a highly conserved cellular degradation pathway which is crucial for various cellular processes. The autophagic process is subdivided in the initiation, autophagosome maturation and lysosomal degradation phases and involves more than forty core and accessory autophagy-related (ATG) proteins. Autophagy 8 (ATG8, in mammals LC3) is a well-established marker of autophagy and is linked to the autophagic membrane from initiation until fusion with the lysosome. We generated single and double knock-out mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 84 publications
3
22
1
Order By: Relevance
“…During growth in nutrient‐rich media, many of the D. discoideum autophagy genes appear to be dispensable (Otto et al, , ). Known exceptions to this are atg8a and atg9 , where their loss leads to reduced growth (Tung et al, ; Messling et al, ). Atg9 is found on distinct Golgi‐derived vesicles that are a source of autophagosomal membrane (they fuse to the autophagosomal outer membrane) and it is consequently involved in forming autophagosomes (Orsi et al, ; Yamamoto et al, ).…”
Section: Autophagy During Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During growth in nutrient‐rich media, many of the D. discoideum autophagy genes appear to be dispensable (Otto et al, , ). Known exceptions to this are atg8a and atg9 , where their loss leads to reduced growth (Tung et al, ; Messling et al, ). Atg9 is found on distinct Golgi‐derived vesicles that are a source of autophagosomal membrane (they fuse to the autophagosomal outer membrane) and it is consequently involved in forming autophagosomes (Orsi et al, ; Yamamoto et al, ).…”
Section: Autophagy During Growth and Developmentmentioning
confidence: 99%
“…This signalling mechanism may also initiate developmental autophagy in D. discoideum (Otto et al, ). The independent loss of atg5 , atg6 , atg7 , atg8a , atg9 or atg101 leads to multi‐tipped aggregates (Otto et al, ; Calvo‐Garrido et al, ; Tung et al, ; Messling et al, ). Multi‐tipped aggregates are a characteristic phenotype of D. discoideum autophagy mutants, and this has been used to identify other autophagy‐regulating proteins in D. discoideum multiple tip mutations (e.g.…”
Section: Autophagy During Growth and Developmentmentioning
confidence: 99%
“…As a consequence, autophagy malfunction generally results in reduced cell survival upon nitrogen starvation and in developmental abnormalities in the affected strains, which also supports the identification of autophagy-deficient mutants in the laboratory (Fischer et al, 2019, King et al, 2013, Mesquita et al, 2017, Otto et al, 2003. The developmental phenotypes range from a complete lack of aggregation to the formation of extremely small and crippled fruiting bodies with drastically reduced spore viability (Calvo-Garrido et al, 2010, Fischer et al, 2019, Mesquita et al, 2015, Messling et al, 2017, Otto et al, 2003, Otto et al, 2004, Tung et al, 2010, Xiong et al, 2015. Differences in the importance of the respective autophagy proteins for the functioning of autophagy and additional non-autophagic functions for some of these proteins are likely responsible for the diverse observed phenotypes (Fischer et al, 2019).…”
Section: Dictyostelium Discoideum An Excellent Model System For Autopmentioning
confidence: 62%
“…D. discoideum harbours two paralogues, ATG8a and ATG8b, which have distinct functions in canonical autophagy. It was shown that they associate to the autophagosome in succession and that ATG8b mainly localises at the outer membrane of the autophagosome while ATG8a is mainly present at the inner membrane (Matthias et al, 2016, Messling et al, 2017. This differential localisation supports a more prominent role for ATG8b as an adapter for the autophagy machinery and in autophagosome lysosome fusion while ATG8a appears to function mainly as a binding partner for autophagy receptors.…”
Section: Main Autophagy-related Proteins In a Selection Of Model Orgamentioning
confidence: 88%
See 1 more Smart Citation